Approximation algorithms for solving multi-objective optimization problems - Babikir, Gais Alhadi (Gezira Journal of Engineering and Applied Sciences, 2022)
This paper tries to cover the main aspects/properties related to scheduling problems, approximation algorithms, and multi-objective combinatorial optimization. Then, we try to describe the main techniques that can be used to solve such problems. In this paper, the reviews results relate to multi-objective optimization problems, exact and approximation search, with the aim of getting all Pareto optimal solutions for some NP-hard problems.